'Loneliness in the city': examining socio-economics, loneliness and poor health in the North East of England. (December 2018) - Macdonald, S.J.; Nixon, J.; Deacon, L.
Abstract: Objectives: The aim of this study was to discover whether lower socio-economic status is associated with increased experiences of loneliness and isolation. The research subsequently determined whether this relationship impacted health inequalities. Study design: The study used a cross-sectional, self-reported survey collecting information on loneliness, isolation and poor health (n = 680). The survey was administered through Sunderland District Council in 2016–2017, and data were analysed at The University of Sunderland. Methods: The study used a quantitative approach, and data were analysed using descriptive statistics, engaging in univariate, bivariate and multivariate levels of analysis. Results: A number of significant findings emerged from the data analysis, linking lower socio-economic status to experiences of loneliness ( P = 0.000) and social isolation ( P = 0.000). When determining if social isolation and socio-economics had a detrimental impact on a person's health, no statistical association was discovered ( P = 0.098). Yet, there was a significant relationship concerning socio-economic status, loneliness and poor health ( P = 0.026). Conclusions: The authors have identified a number of associations within the data with reference to isolation, loneliness and poor health. Therefore, participants from a lower socio-economic group experienced disproportionately high levels of social isolation and emotional loneliness when compared with other socio-economic groups. The data also demonstrate that participants who experienced loneliness, and who were from a lower socio-economic background, were consistently more likely to report poor health than those from other socio-economic backgrounds. Highlights: This article examines the impact of loneliness and isolation on communities within the North East of England. People with a household annual income of below £10, 000 experienced disproportionately high levels of loneliness. The findings present evidence that socio-economics and loneliness have a detrimental impact on a person's health.